2010
DOI: 10.1111/j.1574-6968.2010.01936.x
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruziamino acid transporter TcAAAP411 mediates arginine uptake in yeasts

Abstract: Trypanosoma cruzi, the aetiological agent of Chagas' disease, is exposed to extremely different environment conditions during its life cycle, and transporters are key molecules for its adaptive regulation. Amino acids, and particularly arginine, are essential components in T. cruzi metabolism. In this work, a novel T. cruzi arginine permease was identified by screening different members of the AAAP family (amino acid/auxin permeases) in yeast complementation assays using a toxic arginine analogue. One gene can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…Phylogenetic analyses revealed that the TbAAT5 proteins are homologs of the functionally characterized T . cruzi arginine transporter TcAAAP411 (TcCLB.511411.30 [23]; 76–78% similarity) and TcCAT1.1 to TcCAT1.3 [25] (70–76% similarity), but show a lower degree of similarity to the Leishmania arginine transporter LdAAP3 (LdBPK_310910.1 [6,22]; 60–62% similarity) (Fig 1 and S2 Table). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Phylogenetic analyses revealed that the TbAAT5 proteins are homologs of the functionally characterized T . cruzi arginine transporter TcAAAP411 (TcCLB.511411.30 [23]; 76–78% similarity) and TcCAT1.1 to TcCAT1.3 [25] (70–76% similarity), but show a lower degree of similarity to the Leishmania arginine transporter LdAAP3 (LdBPK_310910.1 [6,22]; 60–62% similarity) (Fig 1 and S2 Table). …”
Section: Resultsmentioning
confidence: 99%
“…cruzi and L . donovani : TcAAAP411, (TcCLB.511411.30 [23]), TcAAP7 (TcCLB.511545.80 [24]), TcCAT1.1, TcCAT1.2, TcCAT1.3 (TcCLB.506153.10, TcCLB.506153.20, TcCLB.506053.10 [25]); LdAAP7 (LdBPK_322800.1 [24]) and LdAAP3 (LdBPK_310910.1 [22]). Further shown are AAP7 in L .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations